Aplikasi Perpustakaan Menggunakan Pendekatan Customer Relationship Management (CRM) (Studi Kasus SMPN 196 Jakarta Timur) - Muhamad Irsan (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
A library system is designed to be directly used by students in borrowing books. SMPN 196 is located in East Jakarta. It doesn’t have a library system that is used to process transactions, including the process of borrowing up to the returning of books by the students. Therefore, a desktop application is needed tofacilitatethe borrowing or returning of books by the students. This research is an Applied Research in whichdata are collected by direct observation, library research and interview methods. The library system model is developed using Customer Relationship Management (CRM) approach. The Modeling used to analyze and design the information system is Object-Oriented Analysis and Design with Unified Modeling Language (UML). Validation test applies Focus Group Discussion. The Quality of the resulted software is tested based on four characteristics of software quality model of ISO 9126: functionality, reliability, usability and efficiency, with a quisioner method and software testing technique using Software Testing Webserver Stress Tool 7. The Library Desktop System Prototype is expected to contribute to SMPN 196 and to service students, so that the desired information can be quickly and accurately obtained and the relationship with the students can be improved.